2009
DOI: 10.2353/ajpath.2009.080677
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Myeloid Cell Transcriptional and Proteomic Responses to Periodontopathogenic Porphyromonas gingivalis

Abstract: Long-lived monocytes, macrophages, and dendritic cells (DCs) are Toll-like receptor-expressing, antigenpresenting cells derived from a common myeloid lineage that play key roles in innate and adaptive immune responses. Based on immunohistochemical and molecular analyses of inflamed tissues from patients with chronic destructive periodontal disease, these cells, found in the inflammatory infiltrate, may drive the progressive periodontal pathogenesis. To investigate early transcriptional signatures and subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 66 publications
2
57
0
Order By: Relevance
“…Based on this analysis, IFN-␣-induced genes above the red line and implicated in defense against HIV are listed in Table 2. Although LPS did not substantially up-regulate antiviral genes such as OAS or MX1, it did stimulate IFN-␤1 greater than 100-fold and other molecules, which may directly or indirectly influence viral infection 27 (see supplemental Table 1). Both IFN-␣ and LPS dramatically up-regulated chemokines, including CCL5, which may influence HIV entry by competing for coreceptor binding, but in this study, we did not focus on the plethora of shared genes found within the lines of identity or unique to LPS.…”
Section: Dissociation Of Activation-induced Genes From Ifn-␣-specificmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on this analysis, IFN-␣-induced genes above the red line and implicated in defense against HIV are listed in Table 2. Although LPS did not substantially up-regulate antiviral genes such as OAS or MX1, it did stimulate IFN-␤1 greater than 100-fold and other molecules, which may directly or indirectly influence viral infection 27 (see supplemental Table 1). Both IFN-␣ and LPS dramatically up-regulated chemokines, including CCL5, which may influence HIV entry by competing for coreceptor binding, but in this study, we did not focus on the plethora of shared genes found within the lines of identity or unique to LPS.…”
Section: Dissociation Of Activation-induced Genes From Ifn-␣-specificmentioning
confidence: 99%
“…Moreover, cytokine and cytokine-related genes were also early macrophage IFN-␣ targets: pentraxin-related gene (PTX3), TNF (ligand) superfamily member 10 (TRAIL), IL-7R, TNF superfamily member 2 (TNF-␣), TNFAIP2, TNFAIP3 interacting protein 3, TNF receptor-associated factor 1 (TRAF1), and IL-6 (IFN-␤2), Epstein-Barr virus-induced 3 (EBI3), IL-12B(p40), IL-1B, and IL-15 (Ͼ 10-fold), along with other proinflammatory and/or potentially toxic molecules, including indoleamine(2,3)-dioxygenase (IDO) and GTP cyclohydrolase I (GCHI), are involved in neopterin production. 29 Only a limited number of probe sets 27 were down-regulated in macrophages upon exposure to IFN-␣ (see supplemental Table 1). …”
Section: Ifn-␣-induced Macrophage Transcriptional Profile By Microarrmentioning
confidence: 99%
See 3 more Smart Citations